Triazole-Enabled Ruthenium(II) Carboxylate-Catalyzed C–H Arylation with Electron-Deficient Aryl Halides - Rogge, Torben; Müller, Thomas; Simon, Hendrik; Hou, Xiaoyan; Wagschal, Simon; Broggini, Diego; Ackermann, Lutz (Synlett, 2021)
A triazole-directed direct C–H arylation of arenes with electron-deficient aryl halides or a synthetically useful pyrimidyl chloride was achieved through ruthenium catalysis. Our novel strategy provides operationally simple and environmentally benign access to highly functionalized hetarenes, avoiding the use of strong organometallic bases. Detailed studies revealed a significant effect of the phosphine ligand, thereby permitting the reaction to occur with excellent levels of chemo- and position selectivity.
Keywords: C–H bond activation; arylation; ruthenium catalysis; hetarenes; aryl halides